The Evaluation of Laparoscopic Hysterectomies in Our Clinic - Murat Ekmez (Haseki Tıp Bülteni, 2017)
Aim: This study was to retrospectively evaluate the results of 74 patients who underwent laparoscopic hysterectomy (LH). Methods: The subjects included 74 patients operated in the Department of Obstetrics and Gynecology at Haseki Training and Research Hospital. Total LH were performed for various indications between November 2010 and November 2016. Indications for total LH, method of operation, intraoperative and postoperative complications, duration of the operation, length of hospital stay, and blood loss in patients who underwent total LH were retrospectively evaluated. Results: Seventy four patients were included in our study. The mean age was 47.2±3 years. The mean operation time was 138.4±44 minutes and the mean length of hospital stay was 3.1±1.7 days. The most common indication for LH procedure was abnormal uterine bleeding (25.9%). The average difference between preoperative and postoperative hematocrit values was 4.3%. Major complication rate was 5.3% and minor complication rate was 5.4%. Conclusion: LH is a safe and effective procedure with a low rate of complications in experienced hands in the management of benign gynecological conditions.